[Rezension von: Hess, Katja, Rhetor, Philosoph, Geistträger : die Bildungsthematik in der lukanischen Paulusdarstellung] - Heijer, Arco den 1989-; Hess, Katja (2020)
This revised dissertation argues that Luke wrote Acts to counter the prejudice that Christianity was a movement of uneducated people by presenting Paul as orator and philosopher. The strengths of the work lie in the analysis of key lexemes associated with rhetorical and philosophical education and in the careful exegesis of the presentation of Paul in central episodes of Acts. (English)
Keywords: Rezension